Fibre-optical calibration of position sensors for Planck-Balances - Germanow, Philipp; Rogge, Norbert; Hausotte, Tino; Froehlich, Thomas (Technisches Messen, 2021)
For the kibble calibration of EMFC systems, the velocity of the actuator coil and the induced coil voltage must be measured during the movement relative to the magnetic field. Commonly the velocity is determined by the position measured over time. As an alternative to an interferometric measurement, a fibre-optic sensor for calibrating EMFC-typical, optical position sensors is presented. The shown fibre optic sensor, as well as the theoretically described, calibration were metrologically validated on a Planck balance. In a direct comparison with a commercial interferometer, deviations of less than 60 nm were achieved over a range of motion of +/- 12 mu m.
CRIS-Team WoS Importer:2021-12-03